Understanding Ethnic and Cultural Diversity: Evidence from Puma - Sharma, Narayan P. (Gipan, 2017)
The most significant and most obvious factor behind the growth of ethnic and cultural diversity in Nepal, is of course, the country’s multilingual context. Multicultural context, in turn, reflects the cultural and linguistic diversity, and social thinking of the period during which the context came into existence. We can argue that cultural and ethnic diversity has always been a source of strength and unity in Nepali society. This article addresses the ethnic and cultural diversity of the Puma people. The future of Nepal will be even more ethnically and culturally diverse than it is today.